2018
DOI: 10.1039/c8ra08557a
|View full text |Cite
|
Sign up to set email alerts
|

Tunable two-dimensional polarization grating using a self-organized micropixelated liquid crystal structure

Abstract: A micro-pixelated pattern of a nematic liquid crystal formed by self-organization of topological defects is shown to work as a tunable two-dimensional optical grating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The spacing between the neighboring defects, and hence the unit size of the pattern, depends on the frequency and the amplitude of the applied AC field, as well as on the cell gap and on the material properties of the LC. By patterning the electrodes or using optical tweezer, arrays created in this way have been made sufficiently regular to generate well‐defined 2D diffraction patterns . However, there are crucial shortcomings to overcome in order for this system to be useful as a diffraction grating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spacing between the neighboring defects, and hence the unit size of the pattern, depends on the frequency and the amplitude of the applied AC field, as well as on the cell gap and on the material properties of the LC. By patterning the electrodes or using optical tweezer, arrays created in this way have been made sufficiently regular to generate well‐defined 2D diffraction patterns . However, there are crucial shortcomings to overcome in order for this system to be useful as a diffraction grating.…”
Section: Introductionmentioning
confidence: 99%
“…Here, besides expanding on the ability to control the regularity and length‐scale of the system, we demonstrate a technique to create and dynamically control patterns of arbitrary complexity to be used as 2D diffraction gratings. To date, 2D LC‐based gratings have been obtained by various approaches, such as superposing multiple 1D arrays, modulating the LC alignment with photopatterning, using the spontaneous periodic undulations in cholesteric LCs or creating field‐induced 2D umbilical defect arrays . In some of these approaches, the dynamic tunability of the 2D diffraction pattern is achieved by tuning each 1D LC grating or by mechanically changing the angle of the polarizers, thus changing the diffraction angle or the shape of diffraction patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the 2D PGs fabricated based on polarization-sensitive materials, Y. Sasaki et al reported a tunable 2D PG obtained from a micro-pixelated LC structure in 2018 [56,57]. By applying a micro-pixelated electric field to a homeotropically aligned nematic LC with negative dielectric anisotropy and ionic additives, as designed in Figure 12a, umbilical defects were formed, and a square array of a 2D micropattern was self-organized (Figure 12b).…”
Section: Micro-pixelated Lc Structuresmentioning
confidence: 99%
“…The second type of 2D PGs was composed of self-organized micropixelated LC structures, which was fabricated based on cross-assembled substrates with stripe-patterned ITO coatings. 20 The diffraction efficiency of the first and second orders could achieve 87%, but the diffraction patterns could not be controlled by the incident polarization state, lacking a degree of tunability. The third type is based on multibeam interference.…”
Section: ■ Introductionmentioning
confidence: 99%